Life story therapy with traumatized children : a model for practice - Rose, Richard, 1965- (Jessica Kingsley Publishers, 2012)
Life Story Therapy is an approach designed to enable children to explore, question and understand the past events of their lives. It aims to secure their future through strengthening attachment with their carers and providing the opportunity to develop a healthy sense of self and a feeling of wellbeing. This comprehensive overview lays out the theory underlying life story therapy, including an accessible explanation of contemporary research in neurobiology and trauma. Featuring tried and tested ideas, with tools and templates illustrated through instructive case studies, the author identifies.